Applying the Hierarchy of Controls: What Occupational Safety Can Teach us About Safely Navigating the Next Phase of the Global COVID-19 Pandemic - Neil J. Sehgal; Donald K. Milton (Frontiers in Public Health, 2021)
Eighteen months into the COVID-19 pandemic, and as the world struggles with global vaccine equity, emerging variants, and the reality that eradication is years away at soonest, we add to notion of “layered defenses” proposing a conceptual model for better understanding the differential applicability and effectiveness of precautions against SARS-CoV-2 transmission. The prevailing adaptation of Reason's Swiss cheese model conceives of all defensive layers as equally protective, when in reality some are more effective than others. Adapting the hierarchy of controls framework from occupational safety provides a better framework for understanding the relative benefit of different hazard control strategies to minimize the spread of SARS-CoV-2.